2016
DOI: 10.1111/mcn.12367
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal lipid‐based nutritional supplementation with fetal growth in rural Gambia

Abstract: Prenatal supplementation with protein‐energy (PE) and/or multiple‐micronutrients (MMNs) may improve fetal growth, but trials of lipid‐based nutritional supplements (LNSs) have reported inconsistent results. We conducted a post‐hoc analysis of non‐primary outcomes in a trial in Gambia, with the aim to test the associations of LNS with fetal growth and explore how efficacy varies depending on nutritional status. The sample comprised 620 pregnant women in an individually randomized, partially blinded trial with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(74 citation statements)
references
References 38 publications
1
73
0
Order By: Relevance
“…On abstract screening, 61 articles were selected for full-text screening and, at the same time, eight articles were included through cross-referencing. Fifteen studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were included for data extraction ( Figure S1). All included trials studied healthy pregnant women at varying gestational ages in LMIC settings.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…On abstract screening, 61 articles were selected for full-text screening and, at the same time, eight articles were included through cross-referencing. Fifteen studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were included for data extraction ( Figure S1). All included trials studied healthy pregnant women at varying gestational ages in LMIC settings.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies included both urban [26,28,32,35] and rural [21,[23][24][25]29,31,33,34] settings, with three studies not specifying their setting [22,27,30]. The characteristics of included studies are briefly mentioned in Table S3.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous trials have examined the effect of multiple micronutrient supplementation during pregnancy on birth outcomes (Brough, Rees, Crawford, Morton, & Dorman, 2010;Osrin et al, 2005;Zagré, Desplats, Adou, Mamadoultaibou, & Aguayo, 2007), but literature on the effect of supplementation on fetal biometry is scarce. A randomised controlled trial in The Gambia showed that a prenatal lipid-based nutritional supplement had no effect on fetal growth overall, but that fetal measurements at 30-week gestation were larger in the dry season among women receiving protein and energy compared with those receiving multiple micronutrients alone or with protein and energy and multiple micronutrients combined (Johnson et al, 2016). A trial in Peru showed a positive effect of prenatal zinc supplementation on FL (Merialdi et al, 2004); however, the quantity of zinc used (25 mg) was more than 27 times higher than that in our food-based supplement (0.9 mg).…”
Section: Figurementioning
confidence: 99%